Synthesis and application of large-area graphene stacks - Wirtz, Christian (Trinity College (Dublin, Ireland). School of Chemistry, 2015)
Research of two-dimensional nanomaterials has been significant since the discovery of graphene in 2004. Really one or few atoms thick but often micrometres in lateral size, these materials exhibit unique properties such as high mechanical strength, transparency, uncommon electric and thermal conductivity and previously unexplored quantum effects. Several hundreds of these materials have now been isolated. This field of research is still very young and a lot of work has yet to be done to fully explore the properties of these materials to allow for their incorporation into new and existing technology. This thesis describes work performed in pursuit of that goal. The main focus was on graphene but some work was also done on MoS2 and WS2. Firstly, a method for synthesising large areas of high-quality graphene was investigated. This was done by chemical vapour deposition from ethene. The method was optimised by statistical design and yielded a process at 850 °C, 200 °C lower than standard processes, that produced patterned monolayer graphene on copper with large sample size. The graphene films consisted of flakes approximately 1 μm in diameter, showed Raman signatures close to the ideal values and exhibited hole and electron mobilities of 1100 cm2V-1s-1 and 700 cm2V-1s-1 respectively. The reduced temperature allowed for better reproducibility and reduced cost. Secondly, this graphene was used to fabricate effective oxygen gas diffusion barriers. In contrast to discouraging reports on large-area graphene coatings published in the past, a modified stacking method allowed three layers of graphene (~1 nm thick) to perform on par with 150 μm PET, a well-established barrier polymer. Its inherent barrier performance was 1.10 x 10-7 barrer which is equal to the standard coating materials SiO2 and Al2O3 of that thickness. Its other extraordinary properties like conductivity, transparency and flexibility, should easily find applications, for example in organic light emitting diodes which require extremely good diffusion barriers that are transparent and ideally conduct electricity. In collaboration with Philips corporation, the graphene stacks were shown to outperform the industrial standard electrode ITO. Further investigation towards functional stacks with 2D materials led to the discovery of signal enhancement in Raman scattering of graphene intercalated with perylene-based molecules. This effect had not been reported previously and though it can be consistently reproduced, its origins remain unclear. Finally the processability of MoS2 and WS2 single crystal layers was investigated. A layer-dependent atomic layer deposition process was developed which allows for coverage of all layers except for the monolayer with AI2O3. This paves the way for vertical device structures that require the unique properties of the monolayer only. In addition, a reliable seeding mechanism via non-covalent functionalisation with perylene bisimides was developed for anchoring deposition even on the monolayer, providing a major step forward in the integration of two-dimensional materials in modern electronics.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.